Transatlantic conversations: the art of the interview in Britain and America - Roach, R (2014)
This thesis assesses the role of the interview form within literature from the late nineteenth century to the present day. The project contends that the interview, although styling itself as a revealing, authentic, private confession, is a genre of life writing that deeply troubles the model of singular Romantic authorship that it simultaneously promotes. The thesis argues that the interview has been a key site for negotiating conceptions of authorship since its inauguration. Exploring issues of publicity, life writing and gossip, through nineteenth-century newspaper depictions of scandals (chapter one), I argue that the act of interview publication is a staging of the speaking self in the public sphere. In chapter two I triangulate discussions of journalism, celebrity and material modernism to argue that the characteristic modernist authorial persona, far from being revolutionary, avant-garde or iconoclastic, was in fact deeply retrograde. Chapter three examines how the interview operated as a negotiation of the study, the marketplace and the middlebrow in the 1930s, with reference to the popular Everyman magazine series “How Writers Work.” The development of an interrogative interview model in the postwar era forms the subject of chapter four, as I demonstrate how the backdrop of the Cold War transformed the ways in which writers as diverse as Ezra Pound and the Beat poets responded to the interview in their work. The penultimate chapter argues that the Paris Review interview offers a hitherto unrecognised link between New Criticism and New Journalism and can revitalise discussions around the historical institutionalisation of literary studies. Chapter six considers the interview’s prominent contemporary position within world literature as a purveyor of literary value and archive of global cultural memory. Overall, the project illustrates how central the interview has been in the cultural construction of authorship in the last 150 years.